Gilles de La Tourette syndrome: the contribution of Guinon - Teive, Hélio Afonso Ghizoni; Germiniani, Francisco M. Branco; Coletta, Marcus Vinícius Della; Camargo, Carlos Henrique Ferreira; Coutinho, Léo; Walusinski, Olivier (Arquivos de Neuro-Psiquiatria, 2025)
We review the contributions of Georges Guinon, an eminent pupil of Professor Jean-Martin Charcot, to the clinical description of Gilles de La Tourette syndrome, including phenomenological definitions and the occurrence of psychiatric findings such as obsessive-compulsive behavior.
Keywords: Neurology; Movement Disorders; Tics; Tourette Syndrome; History; 19th Century